Penguatan Digitalisasi Pemasaran UMKM Teman Lafarku melalui Pembuatan Website Company Profile dan Media Promosi Visual - Ariana Hechalina Ardiansyah; Dita Ramadhani Tianto; Siti Nafiatul Fauziah; Terrafel Agung Safitri; Siti Nur Faizah (PT. Karya Inovatif Nusantara, 2026)
UMKM Teman Lafarku faces challenges in promoting its products digitally due to the lack of professional and structured online media. This community service program aims to support the digitalization of UMKM marketing through the development of a company profile website and promotionalbannerdesigns,alongwithusersocializationforthebusinessowner.Themethodsapplied include needs observation and analysis, digital solution design, and implementation of a company profilewebsitefeaturingbusinessinformation,productgalleries,andcontactdetailsusingHTML,CSS, and Bootstrap technologies, as well as banner design creation using Canva. In addition, socialization and assistance activities were conducted for 2–3 hours, focusing on website content management and basic maintenance. The results indicate that the website and promotional banners were successfully implementedandcanbemanagedindependentlybytheUMKMowner.Theavailabilityofthesedigital media enhances business visibility, improves professional branding, and expands marketing reach. Therefore, this community service activity contributes to strengthening UMKM competitiveness through simple, effective, and sustainable digital marketing, with recommendations for future development of advanced features such as e-commerce integration.